DIRECTIONS OF USE OF SECONDARY RAW MATERIALS IN LIGHT INDUSTRY - ISHCHUK, TETIANA; IVANISHENA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The growth of textile production leads to an increase in waste, putting significant pressure on natural resources and ecosystems. The dependence on primary raw materials such as cotton, wool and polyester contributes to resource depletion and increased carbon dioxide emissions. In contrast, secondary raw materials, including recycled plastic bottles, textile waste and paper fibers, offer a promising solution to reduce environmental impact by minimizing waste and dependence on non-renewable resources. This paper analyzes the dynamics and main research directions of the use of secondary raw materials in light industry. A review of scientific publications in the Scopus database showed that the largest number of publications is devoted to secondary raw materials in the fashion industry, which indicates a growing interest in recycling practices in this context. The search term “recycled paper” AND “textile” accounted for 77.1% of all related searches, demonstrating its importance as an environmentally friendly material in textile manufacturing. The use of recycled materials promotes the principles of a circular economy, increases resource efficiency, and reduces the environmental footprint of light industry. Recycled raw materials include recycled PET bottles, cotton fibers, and leather, each of which offers unique benefits and challenges for incorporation into manufacturing processes. The transition to recycled raw materials not only addresses environmental concerns, but also aligns with global efforts to reduce resource use and waste generation.